Transplantasi Organ Tubuh Ginjal Dalam Perspektif Kebijakan Kriminal - Ayu Linanda; Iva Yulia Munawarah; Metalianda; Siti Indah Kurnia Sari (LPPM STIH Awang Long, 2020)
Donors are ignorant of the prohibition on the practice of buying and selling body organs both belonging to other people and their own in Article 192 of Law Number 36 Year 2009 concerning Health. making buying and selling of organs with their own for commercial purposes thrives in Indonesia. This is the weak point of law enforcement against buying and selling of human organs, especially buying and selling of kidney organs. Therefore it is necessary to carry out further research on the act of transplanting one's own kidney organs for commercial purposes as an illustration of the upcoming criminal policy regarding the act of transplanting one's own kidney organs for commercial purposes. This research is a normative juridical legal research, namely analyzing a legal issue to find concrete law applied in resolving a particular legal case. The technique used in this research is to make an inventory of primary legal materials, secondary legal materials, and tertiary legal materials, and this type of research uses a statute approach with data analysis methods using descriptive methods (descriptive research). The targeted output is in the form of reputable international scientific articles.